Political philosophy and Australian far-right media: A critical discourse analysis of The Unshackled and XYZ. (April 2021) - Richards, Imogen; Rae, Maria; Vergani, Matteo; Jones, Callum
A 21st-century growth in prevalence of extreme right-wing nationalism and social conservatism in Australia, Europe, and America, in certain respects belies the positive impacts of online, new, and alternative forms of global media. Cross-national forms of 'far-right activism' are unconfined to their host nations; individuals and organisations campaign on the basis of ethno-cultural separatism, while capitalising on internet-based affordances for communication and ideological cross-fertilisation. Right-wing revolutionary ideas disseminated in this media, to this end, embody politico-cultural aims that can only be understood with attention to their philosophical underpinnings. Drawing on a dataset of articles from the pseudo-news websites, XYZ and The Unshackled, this paper investigates the representation of different rightist political philosophical traditions in contemporary Australia-based far-right media. A critical discourse and content analysis reveal XYZ and TU's engagement with various traditions, from Nietzsche and the Conservative Revolution, to the European New Right and neo-Nazism.